Comparison of Reported Antibiotic Treatment in Chicken Farming and Antibiotic-Resistant (E. coli) in Commercial Poultry Meat - Amir Gomaa; Sauad Abdulhadi; Najah Mohamad; Abdulsalam Saleh (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the prevalence and antimicrobial resistance of Escherichia coli in poultry meat sold in Al Bayda, Libya. A total of 37 chicken meat samples were analyzed for resistance to 12 antibiotics, using the disk diffusion method. The results indicated high resistance rates, particularly to ampicillin, ampicillin-sulbactam, cefazolin, and tetracycline, with 48% of the isolates exhibiting multidrug resistance. Conventionally reared poultry showed significantly higher resistance to gentamicin, commonly used in egg vaccines. The study found no significant differences in resistance across production categories, but brand-specific factors were strongly associated with resistance levels. These findings suggest that antibiotic use in poultry production, particularly in conventional systems, contributes to increased resistance, emphasizing the need for improved regulations and monitoring of antibiotic use across all stages of production to ensure food safety and reduce the spread of resistance. تبحث هذه الدراسة في انتشار مقاومة المضادات الحيوية لبكتيريا الإشريكية القولونية في لحوم الدواجن المباعة في البيضاء، ليبيا. تم تحليل إجمالي 37 عينة من لحوم الدجاج بحثًا عن مقاومة 12 مضادًا حيويًا، باستخدام طريقة الانتشار القرصي. أشارت النتائج إلى معدلات مقاومة عالية، وخاصة للأمبيسلين، والأمبيسلين-سولباكتام، والسيفازولين، والتتراسيكلين، حيث أظهرت 48٪ من العزلات مقاومة متعددة للأدوية. أظهرت الدواجن التي يتم تربيتها تقليديًا مقاومة أعلى بكثير للجنتاميسين، المستخدم عادة في لقاحات البيض. لم تجد الدراسة أي اختلافات كبيرة في المقاومة عبر فئات الإنتاج، لكن العوامل الخاصة بالعلامة التجارية كانت مرتبطة بقوة بمستويات المقاومة. تشير هذه النتائج إلى أن استخدام المضادات الحيوية في إنتاج الدواجن، وخاصة في الأنظمة التقليدية، يساهم في زيادة المقاومة، مما يؤكد على الحاجة إلى تحسين اللوائح ومراقبة استخدام المضادات الحيوية في جميع مراحل الإنتاج لضمان سلامة الغذاء والحد من انتشار المقاومة